Reinstatement of Distantasca Dworakowska (Hemiptera: Cicadellidae: Typhlocybinae: Empoascini) as a valid genus with new species and new combinations - Liu, Yang; Fletcher, Murray J.; Zhang, Ya-Lin (Zootaxa, 2014)
Distantasca Dworakowska originally established as a genus but more recently has been treated as a subgenus of Empoasca Walsh. Here we reinstate Distantasca as a valid genus and provide a revised diagnosis. New combinations created are Distantasca atika (Dworakowska), n. comb., Distantasca barawa (Dworakowska), n. comb., Distantasca bulbosa (Dworakowska), n. comb., Distantasca latava (Dworakowska), n. comb., Distantasca latibasis (Zhang & Liu), n. comb., Distantasca paraterminalis (Qin & Zhang), n. comb., Distantasca riora (Dworakowska), n. comb., Distantasca rokasa (Dworakowska), n. comb., Distantasca serratipenis (Qin & Zhang), n. comb., Distantasca tiaca (Dworakowska), n. comb., Distantasca tna (Dworakowska), n. comb., Distantasca tuberculata (Zhang & Liu), n. comb., all from Empoasca (Distantasca). Distantasca terminalis (Distant) and D. faciata Dworakowska are reinstated from Empoasca (Distantasca). Two new species, Distantasca longihamatilis Zhang & Liu and Distantasca ricina Zhang & Liu spp. nov. are described and illustrated. Empoasca (Empoasca) smithi Fletcher & Donaldson, 1992 is transferred into the genus as Distantasca smithi (Fletcher & Donaldson).